Through the Prism of the Senses : Mediation and New Realities of the Body in Contemporary Performance. Technology, Cognition and Emergent Research-Creation Methodologies - Choinière, Isabelle; Pitozzi, Enrico (Intellect Books, 2019)
This book is a vital contribution to discussions surrounding research creation and the body in relation to digital media, highlighting the ways in which new technologies confront the sensate, somatic body.